Renewable Energy Resources in Nigeria as Panacea to Electricity Inadequacy: A Review - I. B., Ademiloye; A., Olofinjana; B. M., Yusuf; O. S., Adeoye (International Journal For Research In Electronics & Electrical Engineering, 2020)
Energy is vital to the economic growth of every nation of the world. It is universally believed that per energy consumption of electrical energy of nations of the world determines the prosperity of such nations. In Nigeria, power supply to the citizens is inadequate and this is not farfetched from the fact that the growing population cannot withstand the dwindling generated power. The power required by the blotted population outweighs the power generation and this has created a huge gap between power generation and power demand. This paper reviewed the per capita consumption of the developing and the developed nations of the world and the potentials of the available renewable energy in Nigeria with the view of harnessing the resources to make Nigerians have access to electricity. The renewable energy will enhance affordable, available and adequate power supply to consumers as long as the full potentials of renewable energy sources in the country is maximally harnessed. The paper reviewed the sources of renewable energy, average consumption rate and its impact on the economic growth. The methodology used in this paper was the review of existing literature and collection of relevant secondary data for analysis. The paper posited that electricity inadequacy in Nigeria would become history as long as the available resources of renewable energy is fully harnessed which in turn make power supply available for electricity consumers.